2009
DOI: 10.1007/s00464-009-0609-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear factor kappa B and induction of migration inhibitory factor in tumors by surgical stress of laparotomy versus carbon dioxide pneumoperitoneum: an animal experiment

Abstract: After CO(2) pneumoperitoneum, tumors have less TNFalpha and MIF expression and less NFkappaB activity than after laparotomy. This may be associated with less tumor growth, supporting minimal invasive techniques in gastrointestinal oncologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…In addition, local peritoneal cytokines also have a specific role to play in postoperative ileus [22][23][24][25][26], the formation of peritoneal adhesions [27][28][29][30][31][32], and tumor promotion [33][34][35][36][37]. Only two studies identified in the meta-analysis above measured levels of local peritoneal humoral factors, and their results were conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, local peritoneal cytokines also have a specific role to play in postoperative ileus [22][23][24][25][26], the formation of peritoneal adhesions [27][28][29][30][31][32], and tumor promotion [33][34][35][36][37]. Only two studies identified in the meta-analysis above measured levels of local peritoneal humoral factors, and their results were conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the downstream effector of IL-6, NF-jB [45], is activated by the engagement of a 5 b 1 -integrin [57]. IL-6 is considered to be an inducer of this critical regulator of cancer cell invasiveness [58][59][60], and activated NF-jB synergizes with IL-6 gene transcription in a positive feedback loop [45]. Sdc-1 depletion apparently leads to deregulation of this process in MDA-MB-231 cells, consistent with a role for syndecan glycosaminoglycan chainmediated binding of cytokines and their receptors in a coreceptor function for proinflammatory signaling [2,7].…”
mentioning
confidence: 99%
“…Recently, using the same model, we have reported for the first time, to our knowledge, that the surgical impact of laparotomy and CO 2 pneumoperitoneum could enhance the activity of nuclear factor kappa B (NFjB) and the mRNA expression of migration inhibitory factor (MIF) and TNFa in human gastric cancer [25]. Also, this previous study shows the possibility that the tumor growth could be affected not only by the extent of surgical stress but also by the location and the size of tumor.…”
Section: Discussionmentioning
confidence: 99%